Використання інформаційних технологій в дезактивації при знятті з експлуатації АЕС України - Gavrish V.M.; Safonov V.A.; Stelmach D.A. (General Energy Institute of the National Academy of Sciences of Ukraine, 2003)
The article is about NPP power units decommissioning in Ukraine. Problems of RAW management are reviewed. It was shown that there is not methodology of decontamination costs calculation for development of concept and strategy of NPP decommissioning in Ukraine. It was proposed to use program of optimal decontamination technology selection for this purpose.